2022
DOI: 10.3389/fimmu.2022.821681
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic Role of Mesothelium-Derived Chemokine CXCL1 During Unfavorable Peritoneal Tissue Remodeling in Patients Receiving Peritoneal Dialysis as Renal Replacement Therapy

Abstract: Peritoneal dialysis (PD) is a valuable ‘home treatment’ option, even more so during the ongoing Coronavirus pandemic. However, the long-term use of PD is limited by unfavourable tissue remodelling in the peritoneal membrane, which is associated with inflammation-induced angiogenesis. This appears to be driven primarily through vascular endothelial growth factor (VEGF), while the involvement of other angiogenic signaling pathways is still poorly understood. Here, we have identified the crucial contribution of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 75 publications
0
16
0
Order By: Relevance
“…Peritoneal mesothelium-derived chemokines have been recently proposed as potential therapeutic targets. In this sense, CXCL1 induced in MCs in response to IL-17 exposure displays angiogenic activity and can subsequently control the vascular remodeling in dialyzed peritoneum [ 103 ]. The observation of PD patients exhibiting high CXCL1 expression and subsequent density of microvessels opens to new intervening prospective acting to preserve long-term PM integrity and function.…”
Section: Resident Peritoneal Cells: Activation Of Proinflammatory And...mentioning
confidence: 99%
See 1 more Smart Citation
“…Peritoneal mesothelium-derived chemokines have been recently proposed as potential therapeutic targets. In this sense, CXCL1 induced in MCs in response to IL-17 exposure displays angiogenic activity and can subsequently control the vascular remodeling in dialyzed peritoneum [ 103 ]. The observation of PD patients exhibiting high CXCL1 expression and subsequent density of microvessels opens to new intervening prospective acting to preserve long-term PM integrity and function.…”
Section: Resident Peritoneal Cells: Activation Of Proinflammatory And...mentioning
confidence: 99%
“…It is well established, that peritoneal MCs when entering replicative senescence in vitro, secrete large amounts of proangiogenic (VEGF, CXCL1), proinflammatory (IL-6, IL-8, MCP-1/CCL2) and the profibrotic factors TGF-β and connective tissue growth factor (CTGF/CCN2), precisely known as the SASP components ( Figure 2 ) [ 116 ]. Different preclinical studies have demonstrated that these components of the SASP can significantly contribute to adverse peritoneal remodeling during PD by promoting MMT and angiogenesis [ 46 , 103 , 117 , 118 ].…”
Section: Cellular Senescence In the Peritoneummentioning
confidence: 99%
“…During PA formation, the production of inflammatory mediators regulates the ECM [ 43 ]. CXCL1 may be an important pro-angiogenic agent [ 67 ]. Catar et al showed that CXCL1 secreted by PMCs directly promotes human microvascular endothelial tube formation [ 67 ], and VEGF accelerates the PA process by participating in angiogenesis [ 68 , 69 ].…”
Section: The Mechanism Of Pmcs In Promoting Pasmentioning
confidence: 99%
“…CXCL1 may be an important pro-angiogenic agent [ 67 ]. Catar et al showed that CXCL1 secreted by PMCs directly promotes human microvascular endothelial tube formation [ 67 ], and VEGF accelerates the PA process by participating in angiogenesis [ 68 , 69 ]. CXCL1 can also upregulate the expression of PAI-1 and promote fibrin deposition [ 3 ].…”
Section: The Mechanism Of Pmcs In Promoting Pasmentioning
confidence: 99%
“…Dialysis is the most frequently used renal replacement therapy (RRT) for end-stage kidney disease (ESKD) patients. It is estimated that almost 90% of these patients undergo hemodialysis (HD), with the remainder undergoing peritoneal dialysis, 1 although this value can vary between countries/regions, 2 for example, in Mexico where up to 70% of patients receive PD 3 and in Hong-Kong, which has a PD-first policy. 4,5 Conventional HD involves solute diffusion and limited ultrafiltration (weight loss for fluid control and internal filtration) across a high-flux membrane embedded in a hollow-fiber dialyser for 4 h per session.…”
Section: Introductionmentioning
confidence: 99%